The lower hybrid waves driven by inhomogeneous ion-ring distribution - Chibisov, D.V.; Mikhailenko, V.S. (Вопросы атомной науки и техники, 2012)
The electrostatic lower hybrid waves driven by the ion-ring distribution with a radially inhomogeneous density in homogeneous Maxwellian plasma are studied. It is shown that the main mechanism of excitation of instability is the ion-ring current across the magnetic field, although the effect of inhomogeneity of the ion-ring distribution on the conditions of instability also takes place. As a possible mechanism of saturation of instability the scattering of ions of ring distribution by random fluctuations of the electrostatic potential is considered. Исследуются электростатические нижнегибридные волны, обусловленные радиально-неоднородным ионным кольцевым распределением в пространстве скоростей в однородной максвелловской плазме. Показано, что основным механизмом возбуждения неустойчивости является ионный кольцевой ток поперек магнитного поля, хотя на условия неустойчивости также влияет неоднородность ионного кольцевого распределения. В качестве возможного механизма насыщения неустойчивости рассматривается рассеяние ионов кольцевого распределения случайными флуктуациями электростатического потенциала. Досліджуються електростатичні нижньогібридні хвилі, обумовлені радіально-неоднорідним іонним кільцевим розподілом у просторі швидкостей в однорідній максвеллівській плазмі. Показано, що основним механізмом збудження нестійкості є іонний кільцевий струм поперек магнітного поля, хоча на умови нестійкості також впливає неоднорідність іонного кільцевого розподілу. В якості можливого механізму насичення нестійкості розглядається розсіювання іонів кільцевого розподілу випадковими флуктуаціями електростатичного потенціалу.